IMPLEMENTASI VIDEO ANIMASI DALAM PEMBELAJARAN MATEMATIKA PERMULAAN DI TK. DHARMA PUTRA - Ni Wayan Suardiati Putri; Kadek Suryati; Ketut Sepdyana Kartini; Evi Dwi Krisna; Amadeus Veda kanaka (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
In the DHARMA PUTRA kindergarten early age children are invited to play while learning. Playing is done to encourage children to be physically active but still include the required learning materials. Government policy, through the freedom to learn program, requires education units to create fun learning activities so that children feel happy in learning. Even though it's kindergarten. Dharma Putra has implemented a learning model through fun physical activities, but the development of young children currently requires additional learning models. Today's young children are accustomed to using information technology such as computers or smartphones. Even though at school children are not allowed to use smartphones, at home each child is used to being given a smartphone by their parents. This certainly cannot be controlled by the school. With the implementation of Early Mathematics Learning Animation Video activities for young children, it is hoped that they will be able to teach children to use their smartphones to make them more useful. Children will be invited to learn initial mathematics material via computer/smartphone at school.